Life History Traits and Fishery Dynamics of Speckled Shrimp, Metapenaeus monoceros (Fabricius, 1798), Along the Saudi Arabian Red Sea Coast - Sheeja Gireesh; Eyüp Mümtaz Tıraşın; Goutham Bharathi Muthu Palani; Santhosh Kumar Charles; Sirajudheen Thayyil Kadengal; Ronald Grech Santucci; Ricardo Clapis Garla; Zahra Okba; Adel M. S. Adam; Mark Dimech (Biology)
Metapenaeus monoceros is the second most abundant commercially important shrimp species caught along the Saudi Arabian Red Sea coast. However, knowledge of its life history and population dynamics in the region remains limited, posing challenges for sustainable management. This study assessed the growth, maturity, and mortality of M. monoceros based on fishery-independent samples collected from shrimp trawling grounds off Al Qunfudhah and Jizan (October 2022–September 2023). Altogether, 10,859 specimens were examined, with a carapace length (CL) ranging from 7.98 to 49.10 mm and a total weight (W) in the range of 0.41 to 41.28 g. The observed sex ratio was 1.56:1 in favor of females. The CL–W relationship was W = 0.0024∙CL2.58. The seasonalized von Bertalanffy growth parameters were CL∞ = 50.66 mm, K = 0.35 year−1, tanchor = 0.43 years, C = 0.64, and ts = 0.61 years for females, and CL∞ = 38.97 mm, K = 0.55 year−1, tanchor = 0.51 years, C = 0.84, and ts = 0.39 years for males. Females reached their first sexual maturity at 21.12 mm CL. The exploitation rates (0.60 for both sexes) indicated overfishing. Spawning potential ratio analysis showed that the current fishing pressure reduces the spawning stock biomass to 23% of unexploited levels. A 50% reduction in fishing effort, extended seasonal closures, and selective gear modifications are recommended to rebuild the stock and ensure sustainability.